A new spatially scanning 2.7 µm laser hygrometer and new small-scale wind tunnel for direct analysis of the H2O boundary layer structure at single plant leaves - Wunderle, Karl; Rascher, U.; Pieruschka, R.; Schurr, U.; Ebert, Volker (Applied physics. B, Lasers and optics, 2015)
A new spatially scanning TDLAS in situ hygrometer based on a 2.7-µm DFB diode laser was constructed and used to analyse the water vapour concentration boundary layer structure at the surface of a single plant leaf. Using an absorption length of only 5.4 cm, the TDLAS hygrometer permits a H2O vapour concentration resolution of 31 ppmv. This corresponds to a normalized precision of 1.7 ppm m. In order to preserve and control the H2O boundary layer on an individual leaf and to study the boundary layer dependence on the wind speed to which the leaf might be exposed in nature, we also constructed a new, application specific, small-scale, wind tunnel for individual plant leaves. The rectangular, closed-loop tunnel has overall dimensions of 1.2 × 0.6 m and a measurement chamber dimension of 40 × 54 mm (H × W). It allows to generate a laminar flow with a precisely controlled wind speed at the plant leaf surface. Combining honeycombs and a miniaturized compression orifice, we could generate and control stable wind speeds from 0.1 to 0.9 m/s, and a highly laminar and homogeneous flow with an excellent relative spatial homogeneity of 0.969 ± 0.03. Combining the spectrometer and the wind tunnel, we analysed (for the first time) non-invasively the wind speed-dependent vertical structure of the H2O vapour distribution within the boundary layer of a single plant leaf. Using our time-lag-free data acquisition procedure for phase locked signal averaging, we achieved a temporal resolution of 0.2 s for an individual spatial point, while a complete vertical spatial scan at a spatial resolution of 0.18 mm took 77 s. The boundary layer thickness was found to decrease from 6.7 to 3.6 mm at increasing wind speeds of 0.1-0.9 m/s. According to our knowledge, this is the first experimental quantification of wind speed-dependent H2O vapour boundary layer concentration profiles of single plant leaves.
Gesehen am 30.06.2020
Published 07 November 2014